Philippine labor and the economy course guidebook and selected readings - Sibal, Jorge V. (Central Book Supply, 2008)
"Dean Sibal wrote this Guidebook primarily for students, facilitators, tutors and learners in the course on "Labor and the Economy" at UP SOLAIR and in subjects on "Labor Economics" and "Personnel and Industrial Relations" in other schools both at the collegiate and graduate studies levels. It can be used in the traditional face-to-face mode of teaching and facilitating or using the mixed on-line mode."--Preface.